Behavioural reactions of consumers to economic recession - Valášková, Katarína; Klieštik, Tomáš (Business: Theory and Practice, 2015)
The negative effects caused by the economic recession of the recent year, led to the necessity to recognize the changes in the consumer behaviour that may have a lasting impact, and they definitely will. The situation in the Slovak consumer market is described and characterized by the survey which was conduced in 2013. The article also raises three hypotheses considering the basic fact about consumers and their impact on the intensity of behavioural changes. In order to verify our results surveys and studies carried out by many companies in various countries are analyzed in the last chapter.